PENERAPAN METODE SMART (SIMPLE MULTI ATRIBUTTE RATING TECHNIQUE) DALAM PENDUKUNG KEPUTUSAN WARISAN BUDAYA TAKBENDA PROVINSI BENGKULU BERBASIS WEBSITE - Andreswari, Desi; Farady Coastera, Funny; Sarwono, Sarwit; Balqis, Nabilatul (Jurnal Pseudocode, 2024)
This research aims to develop a Decision Support System (DSS) that can provide recommendations for the intangible cultural heritage of Bengkulu Province in accordance with the proposed determination of intangible cultural heritage. This system was designed using UML and implemented in the PHP programming language. This system will determine the recommended intangible cultural heritage using the SMART (Simple Multi Attribute Rating Technique) method. After that, a ranking of intangible cultural heritage recommendations was carried out according to the criteria for the determination form, photos/images, videos, studies, management and substance of intangible cultural heritage using the SMART method. The output of this system is a ranking of recommendations for intangible cultural heritage according to existing alternatives. System testing uses black box testing with 12 pages and 38 scenarios that are tested and produce a success score of 100%. Keywords: Intangible Cultural Heritage, Decision Support System, SMART Method